SWOT ANALYSIS AS A CULINARY DEVELOPMENT STRATEGY FOR BAKSO KONDANG IN SOUTHEAST ACEH - Mustafaruddin, Mustafaruddin; Syahbudi, Muhammad; B Syarbaini, Ahmad Muhaisin (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
The culinary industry is growing in several regions. Famous meatballs are a regional gastronomic highlight. The Kutacane meatball company in Southeast Aceh will be assessed using SWOT analysis in this study. SWOT (Strengths, Weaknesses, Opportunities, Threats) finds internal and external aspects that can affect corporate success. In-depth interviews with business owners, staff, and customers are used in this qualitative case study research. This research found that the EFI Matrix score is 3.14 and the EFE Matrix score is 2.92. The famous Southeast Aceh Regency meatball business's SWOT Analysis, based on internal and external factors, yields four strategies: SO, WO, ST, and WT